Thyroid Cancer: Behavior in Cienfuegos - José Alberto Puerto Lorenzo; Lidia Torres Aja; Eslinda Cabanes Rojas (Revista Finlay)
Foundation: thyroid cancer represents 1 % of the total of all types of cancer. Its incidence seems to increase 4 % each year and it is currently the eighth most frequent cancers in women. Objective: to determine the behavior of thyroid cancer in the Cienfuegos Province for a 5 year period from January 1st 2011 to December 31st 2015. Method: a descriptive study was carried out in 94 patients operated on thyroid cancer in the Surgery Service of the Gustavo Aldereguía Lima Provincial Hospital Cienfuegos during a five year period. The variables analyzed were: age group, municipality of origin, initial symptom of the disease, tumor location, histological variety, clinical stage of the disease and post-surgical complications. A model of data collection was used with the variables of interest for the study and data were represented in tables of frequency, numbers and percentages. Results: thyroid cancer is more frequent in the age group of 41 to 50 years old, papillary histological variety predominated; the right lobule was the most affected. The disease was diagnosed in early stages, the neck volume increase was the most frequently referred symptom by the patients. Transitory recurrent paralysis was the most frequent complication and Aguada de Pasajeros the most affected municipality. Conclusion: thyroid cancer is more frequent in relatively young patients and it is diagnosed at early stages of the disease.